The rock avalanche of Cerro Los Cardos (37° 10′S, 70° 53′ W) in the northern region of the province of Neuquén - González Díaz, E.F. (2005)
A new and important rock avalanche not previously recognized is described, which is located 25 km west of Andacollo town. It shows two scars (northern and southern ones) where the southernmost one is interpreted as the most important, developed in the western flank of a reduced basaltic plain, where at its northern part of Cerro Los Cardos is located. The movement is complex showing several breakaway zones developed into the landslide deposit, considered as secondary scars, all of them, main and secondary ones, have a NW trending. The movement mechanics seems to have started as a planar landslide considering the local almost vertical bedding of the Lileo Formation. However, the concave nature of the breakaway zones allows to infer a rotational movement after the initial stage of sliding. The movement corresponding to the southern breakaway zone was projected as a flux to the south of the Lileo valley, presumably in successive pulses as indicated by the multiple secondary scars. The movement corresponding to the northern break away zone moved to the west and after-wards seems to be controlled by the slope of the valley, moving through to the Palao valley. The western slope of the Palao valley was covered by avalanche deposits corresponding to a run-up. Los Rojos lake is located in a depression presumably generated by the landslide and consequent fracturing of a rock block detached from a Los Cardos's lavic structural plain. Several factors, particularly the structure, favoured the development of the landslide. We propose a seismic trigger for the Los Cardos's avalanche, having into account the regional seismotectonic characteristics (neotectonic front) and the local structure (lineaments, faults). Other landslides, some of them with volume similar to an avalanche deposit, have been included in a regional map. Moreover, modifications to the regional stratigraphy, particularly referred to the volcanic units, are proposed based on morphological criteria. Other geoforms related to other geomorphological processes, fluvial, volcanic and glacial are identified. © 2005 Asociación Geológica Argentina.